2003
DOI: 10.1182/blood-2002-09-2841
|View full text |Cite
|
Sign up to set email alerts
|

Src-family kinase signaling modulates the adhesion ofPlasmodium falciparum on human microvascular endothelium under flow

Abstract: The pathogenicity of Plasmodium falciparum is due to the unique ability of infected erythrocytes (IRBCs) to adhere to vascular endothelium. We investigated whether adhesion of IRBCs to CD36, the major cytoadherence receptor on human dermal microvascular endothelial cells (HDMECs), induces intracellular signaling and regulates adhesion. A recombinant peptide corresponding to the minimal CD36-binding domain from P falciparum erythrocyte membrane protein 1 (PfEMP1), as well as an anti-CD36 monoclonal antibody (mA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 49 publications
3
57
0
Order By: Relevance
“…Previous studies, performed using cultures of human umbilical vein EC, human dermal microvascular EC, human pulmonary EC, or animal cerebral EC lines, have suggested that PRBCs cytoadherence to EC could induce a BBB alteration via activation of intracellular signaling pathways, which leads to changes in the expression of surface adhesion molecule, release of immunoregulatory molecules, and junctions opening (Gillrie et al, 2007;Jenkins et al, 2007;Taoufiq et al, 2008;Yipp et al, 2003). In contrast, in the hCMEC/D3 model, our results showed that alteration of the paracellular permeability can be induced with noncytoadherent PRBCs, as observed in primary brain EC (Tripathi et al, 2007) or even when the PRBCs are not in contact with the cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies, performed using cultures of human umbilical vein EC, human dermal microvascular EC, human pulmonary EC, or animal cerebral EC lines, have suggested that PRBCs cytoadherence to EC could induce a BBB alteration via activation of intracellular signaling pathways, which leads to changes in the expression of surface adhesion molecule, release of immunoregulatory molecules, and junctions opening (Gillrie et al, 2007;Jenkins et al, 2007;Taoufiq et al, 2008;Yipp et al, 2003). In contrast, in the hCMEC/D3 model, our results showed that alteration of the paracellular permeability can be induced with noncytoadherent PRBCs, as observed in primary brain EC (Tripathi et al, 2007) or even when the PRBCs are not in contact with the cells.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this limitation, recent studies have used primary EC from either animal origin, such as porcine (Treeratanapiboon et al, 2005), simian cells (Gay et al, 1995), or human origin from different organs, including skin (Yipp et al, 2003), lung (Taoufiq et al, 2008), and brain (Tripathi et al, 2007). Nevertheless, the procedure of cell isolation remains a delicate and time-consuming step.…”
Section: Introductionmentioning
confidence: 99%
“…Src-family kinase signaling was found to modulate the adhesion of P. falciparum on human microvasculature (Yipp, Robbins et al 2003;Gillrie, Krishnegowda et al 2007). A novel mechanism for the regulation of pRBCs adhesion on human microvascular endothelial cells is through CD36, Src-family kinase, and ectoalkaline phosphatase (Yipp, Robbins et al 2003).…”
Section: Map Kinase/ Src Family Kinase Pathwaymentioning
confidence: 99%
“…In murine models, apoptosis occurs in endothelial cells first, and is followed by neuronal and glia cells (Lackner, Burger et al 2007). P. falciparum-pRBCs increase the expression of ICAM-1 and CD36 (Collins, Read et al 1995;Tripathi, Sullivan et al 2006;Tripathi, Sha et al 2009) which strengthens sequestration, probably through NF-kappa B (Collins, Read et al 1995;Tripathi, Sullivan et al 2006;Tripathi, Sha et al 2009) and MAP Kinase activation (Yipp, Robbins et al 2003). In addition, pRBC adhesion to endothelium was found to up regulate several TNFsuperfamily genes and apoptosis-related genes such as Bad, Bax, caspase-3, SARP2, DFF45/ICAD, IFN-g receptor2, Bcl-w, Bik, and iNOS (Pino, Vouldoukis et al 2003).…”
Section: Endothelial Cells and Parasitized Red Blood Cellsmentioning
confidence: 99%
See 1 more Smart Citation